Joint Effects of Submesoscale Lateral Dispersion and Biological Reactions on Biogeochemical Flux - Lulabel R. Seitz; Mara A. Freilich (Geophysical Research Letters)
Abstract Submesoscale dynamics, operating at spatial scales of O(1−10km) and temporal scales of O(1day), are particularly important for marine ecosystems as they occur on similar timescales as phytoplankton growth, enabling biophysical feedbacks. Lateral stirring at the submesoscale impacts phytoplankton communities by altering nutrient fluxes, spatial heterogeneity, and biodiversity. We formulate an idealized model of phytoplankton growth and transport to understand the key factors driving these biophysical interactions and to determine how the impact of submesoscale dispersion on biogeochemical fluxes depends on flow properties versus biology. By parameterizing the effects of dispersion due to lateral stirring on flux within an eastern boundary current region, we show that enhanced dispersion yields a near‐linear increase in cross‐shore flux, modulated by phytoplankton growth rates and ambient nutrient availability. These findings identify a pathway for improving parameterizations of biogeochemical fluxes, while revealing a source of uncertainty in their prediction by climate models.